Large Campus Network Using hierarchical Model - Mizhir Hasan, Shatha; Ebada Sa’eed, Roa’a (Iraqi Journal of Science, 2023)
This paper presents a hierarchical model of localized company effective when is used in a university campus or site. To highlight the standard criteria for each layer of the model and to prove the positive aspects of this model is the best in use and make the Dell Network as case of study. Through the case of study it has been shown that the expansion of the on-site network does not affect services or bandwidth.